Ruptured ectopic pregnancy in a non-communicating rudimentary horn of a unicornuate uterus: A case report - Kaudel, S (Journal of Chitwan Medical College, 2017)
Uterine rupture in first and second trimester in a non-scarred uterus is usually associated with Mullerian anomalies like rudimentary horn pregnancy. Such rudimentary horn pregnancy is difficult to diagnose antenatally but it carries grave consequences for the mother and fetus. Here is a case of undiagnosed ruptured rudimentary horn pregnancy in unicornuate uterus in Gravida 2 Para 0+1 lady at 18 week gestation who was admitted in Emergency with Shock and diagnosis was confirmed at laparotomy.